2012
DOI: 10.2136/vzj2011.0188
|View full text |Cite
|
Sign up to set email alerts
|

Water Infiltration into a Frozen Soil with Simultaneous Melting of the Frozen Layer

Abstract: Understanding water infiltration into frozen soil is important for preventing soil erosion and managing soil water and nutrients. In this study, we performed a column experiment on infiltration through frozen soil using a variably‐saturated silt loam. Three soil columns (7.8 cm i.d., 35 cm long), with three different initial soil water contents, were cooled from the top to form a frozen layer of the same thickness. The columns were instrumented with 34 thermocouples, seven time‐domain reflectometry (TDR) probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
45
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 34 publications
3
45
0
1
Order By: Relevance
“…However, such models require accurate spatial parameterization of antecedent catchment states [6,7]. One crucial variable that contributes to the overall runoff/infiltration ratio during a rainfall event is soil moisture [8][9][10][11][12][13]. Soil moisture is also a key variable for the complex understanding of hydrological processes in the vadose zone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such models require accurate spatial parameterization of antecedent catchment states [6,7]. One crucial variable that contributes to the overall runoff/infiltration ratio during a rainfall event is soil moisture [8][9][10][11][12][13]. Soil moisture is also a key variable for the complex understanding of hydrological processes in the vadose zone.…”
Section: Introductionmentioning
confidence: 99%
“…Spatially and temporally varying soil moisture has been increasingly used as an input parameter to hydrological and meteorological models as soil moisture plays a crucial role in the surface runoff of water originating from heavy rainfalls [1]. The spatial distribution of soil moisture varies as a function of the spatial distribution of evapotranspiration and precipitation, ultimately influ-enced by topography, soil texture, and land use type [5][6][7][8]. Alternatives to collecting sufficient knowledge on its spatial distribution include high resolution in situ measurement and monitoring [17,18] or satellite remote sensing applications [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…This might indicate that a longer winter period of deep soil freezing prevented the soil surface water content from dissipating vertically, thus retaining the soil moisture at the surface, and driving a high runoff ratio come the spring. It might also indicate that faster infiltration rates and reduced runoff ratios -when the wetting front reached the thawed layer below the frozen layer (Watanabe et al, 2012) -were not reached because the wetting front did not reach thawed soil when the soil was frozen to greater depths. The longer the soil was frozen and the deeper it was frozen, the stronger the soil moisture memory 20 was.…”
mentioning
confidence: 99%
“…Other more recent studies, e.g., Ban et al (2016), have shown that water flows much faster over a frozen slope than over a thawed slope. Watanabe et al (2013) found that the speed of snowmelt and/or rain infiltration into frozen soils is largely dependent on initial water content, frost depth and temperature of the soil. In addition, Yami et al (2012) showed that increasing soil moisture and finer soil structure advance the speed and depth of the freezing front.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Houri et al, 2009;Iwata et al, 2011;Watanabe et al, 2013) and have attempted to link these to changes in soil structure. Until recently, the structural properties of soils had to be inferred from hydraulic measurements (Bodner et al, 2008) or destructive 2D visualisation methods (e.g.…”
Section: Introductionmentioning
confidence: 99%